2008
DOI: 10.1063/1.2939562
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and reliability enhancement of silicon nanocrystal field-effect luminescence from nitride-oxide gate stacks

Abstract: We report on a field-effect light emitting device based on silicon nanocrystals in silicon oxide deposited by plasma-enhanced chemical vapor deposition. The device shows high power efficiency and long lifetime. The power efficiency is enhanced up to ϳ0.1% by the presence of a silicon nitride control layer. The leakage current reduction induced by this nitride buffer effectively increases the power efficiency two orders of magnitude with regard to similarly processed devices with solely oxide. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 17 publications
2
34
0
Order By: Relevance
“…In the case of the MNOS structure, the nitride buffer reduces the device leakage current leading to a better profit of the injected charge that translates into power efficiencies of about 1% and output emission powers of ∼10 nW. It is worth noting the slow variation of the power efficiency with the gate bias in MNOS structures that is attributed to the increase of the FN onset [34].…”
Section: Leds Performancesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the MNOS structure, the nitride buffer reduces the device leakage current leading to a better profit of the injected charge that translates into power efficiencies of about 1% and output emission powers of ∼10 nW. It is worth noting the slow variation of the power efficiency with the gate bias in MNOS structures that is attributed to the increase of the FN onset [34].…”
Section: Leds Performancesmentioning
confidence: 99%
“…The weak emission of sample PD5 is, in contrast to samples PD2 and PD3, associated to the loss of quantum confinement and to the emergence of carrier migration phenomena. Figure 21(c) compares the power efficiency of different deposited and implanted samples to the values obtained from a reference device, with a MNOS (metal nitride oxide semiconductor) configuration that has been recently reported as a highefficiency structure [34]. A thin buffer of pure Si 3 N 4 (∼15 nm) is deposited onto the SRO in order to limit the device leakage current.…”
Section: Leds Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it has been reported that the combination of Si 3 N 4 /SRO structure improves luminescent emission properties [73,74]. Previous studies have also shown that a Si 3 N 4 -SRO bilayer structure improves the operation of light-emiting devices, such as a reduced leakage current, a reduced electric ield on the oxide layer, and results an improvement in eiciency and a longer device life [73][74][75][76].…”
Section: Silicon-rich Nitride/silicon-rich Oxide (Srn/sro) Bilayersmentioning
confidence: 99%
“…Previous studies have also shown that a Si 3 N 4 -SRO bilayer structure improves the operation of light-emiting devices, such as a reduced leakage current, a reduced electric ield on the oxide layer, and results an improvement in eiciency and a longer device life [73][74][75][76]. In this chapter, the efect of a SRN ilm on a SRO ilm (SRN/SRO bilayers) on their optical properties is analyzed.…”
Section: Silicon-rich Nitride/silicon-rich Oxide (Srn/sro) Bilayersmentioning
confidence: 99%